Materials Discovery With Machine Learning and Knowledge Discovery - Oliveira, Osvaldo N.; Oliveira, Maria Cristina F. (Frontiers in Chemistry, 2022)
Machine learning and other artificial intelligence methods are gaining increasing prominence in chemistry and materials sciences, especially for materials design and discovery, and in data analysis of measurements generated by sensors and biosensors. In this paper, we present a perspective on the impact of this use of machine learning, and discuss the prospects of knowledge discovery as an essential step towards a new paradigm of machine-generated knowledge. The reasons why results so far have been limited are given with a discussion of the limitations of machine learning in tasks requiring interpretation. Also discussed is the need to adapt the training of students and scientists in chemistry and materials sciences, to better explore the potential of artificial intelligence capabilities.